Associations between Distal Upper Extremity Job Physical Factors and Psychosocial Measures in a Pooled Study. (18th October 2015) - Thiese, Matthew S.; Hegmann, Kurt T.; Kapellusch, Jay; Merryweather, Andrew; Bao, Stephen; Silverstein, Barbara; Garg, Arun
Abstract : Introduction . There is an increasing body of literature relating musculoskeletal diseases to both job physical exposures and psychosocial outcomes. Relationships between job physical exposure measures and psychosocial factors have not been well examined or quantified. These exploratory analyses evaluate relationships between quantified exposures and psychosocial outcomes. Methods . Individualized quantification of duration, repetition, and force and composite scores of the Strain Index (SI) and the Threshold Limit Value for Hand Activity Level (TLV for HAL) were compared to 10 psychosocial measures. Relationships and predicted probabilities were assessed using ordered logistic regression. Analyses were adjusted for age, BMI, and gender. Results and Discussion . Among 1834 study participants there were multiple statistically significant relationships. In general, as duration, repetition, and force increased, psychosocial factors worsened. However, general health and mental exhaustion improved with increasing job exposures. Depression was most strongly associated with increased repetition, while physical exhaustion was most strongly associated with increased force. SI and TLV for HAL were significantly related to multiple psychosocial factors. These relationships persisted after adjustment for strong confounders. Conclusion . This study quantified multiple associations between job physical exposures and occupational and nonoccupational psychosocial factors. Further research is needed to quantify the impacts on occupational health outcomes.